Sexual violence in the 'manosphere': Antifeminist men's rights discourses on rape - Gotell, Lise; Dutton, Emily (International journal for crime, justice and social democracy, 2016)
This paper explores the role that men's rights activism (MRA) is playing in a contemporary backlash to feminist anti-rape activism. We engage in a discourse analysis of popular MRA websites to reveal a set of interrelated claims, including: that sexual violence, like domestic violence, is a gender-neutral problem; that feminists are responsible for erasing men's experiences of victimization; that false allegations are widespread; and that rape culture is a feminist-produced moral panic. We argue that sexual violence is emerging as a new focus of the men's rights movement, competing with a longstanding emphasis on fathers' rights. The subject of MRA activism has shifted and is becoming less familial and more sexual. MRAs appear to be using the issue of rape to mobilize young men and to exploit their anxieties about shifting consent standards and changing gender norms.